Implementación de una planta procesadora de yogurt en la comunidad Atillo parroquia Cebadas, cantón Guamote, perteneciente a la provincia de Chimborazo - Paña Soldado, Lucía Pilar (2010)
The Atillo community is part of Cebadas County in the Chimborazo province and is located at 3400 meters above sea level. The people of this community mainly produce milk. Up to now, this product has been used as a raw material only for the production of cheese in the “queseras” of Cebadas. Part of the cheese produced is sold commercially and the rest is consumed by the local population. Since there are many “queseras” producing cheese, the supply exceeds demand. Therefore, I propose to diversify the dairy production by introducing yogurt to the market. In order to reach this objective, the implementation of a Yogurt factory in Atillo is essential. Early studies demonstrate that a total inversion of 62.161.72 USD would be required. Initially, USD 47.447,72 will be needed to cover fixed and variable costs. At the beginning, the factory may produce 500 lt/day and it would increase progressively until reaching the goal which is 1100lt/day. Analytical data indicates that it is possible to reach a profit/costs rate of 1.03, a Net Value of USD 24.456,03 and an IRR (Internal Rate of Return) of 45 %.